Training medical students in motivational interviewing using a blended learning approach: a proof-of-concept study - Erschens, Rebecca; Fahse, Bettina; Festl-Wietek, Teresa; Herrmann-Werner, Anne; Keifenheim, Katharina E.; Zipfel, Stephan; Fallgatter, Andreas J.; Velten-Schurian, Kerstin (Frontiers in Psychology, 2023)
Background Difficulties in implementing behavior change in patients with chronic diseases are common in clinical practice. Motivational interviewing (MI) helps clinicians to support patients in overcoming ambivalence while maintaining self-determination. The inclusion of MI in German medical training curricula is still rare. Furthermore, the effects of systematic teaching of MI, especially via blended learning, have hardly been investigated. Methods Medical students participated in three curricular events related to MI, consisting of instructional videos and theoretical and practical components in a blended learning format. The aim of the study was to investigate the effect of teaching MI in students’ medical education. A controlled, non-randomized study was conducted with an intervention group and a control group. Both groups completed questionnaires on their experience and knowledge related to MI, completed a knowledge test and rated their satisfaction with the course. MI was taught in the 6th semester of medical coursework as part of a psychosomatic course, in the 8th semester during a psychiatry course and in the 9th semester during a weekly psychiatry clerkship. Results Data from the intervention group (n = 35) and control group (n = 14) were analyzed, with 65.7% of students participating in all three parts of the curriculum. Overall interest in learning MI was high, with M = 2.92 (SD = 1.00). The results indicate a greater increase in knowledge over time in the intervention group. The majority (62.86%) stated that the curriculum was relevant to their future career. Free-form text responses indicated a high level of satisfaction with practical relevance. Conclusion This study demonstrates the usefulness of an MI curriculum for medical students. The integration of MI into medical curricula is a promising curricular addition to improve doctor-patient communication. Future research should address patient perceptions of MI competencies and the persistence of acquired competencies.